(untitled) (International Journal of Innovative Technologies in Economy, 2023)
The purpose of this study is to reveal the truth by examining the impact of leadership style on financial reporting. This study is confirmatory, descriptive, and causal in nature, aiming to examine how predicted factors influence variables along with other variables. The data used in this study comprise primary data obtained from questionnaires distributed to 100 respondents from various organizations in Indonesia. The unit of observation for this study is the accounting and finance department of each organization. The sampling technique employed is a non-probabilistic technique. Hypotheses were tested using a structural equation model (SEM) with model parameter estimation conducted through the partial least squares (PLS) method. The unobservability of the variables involved and the causal relationships between variables should be considered when selecting an SEM analysis technique. In other words, the underlying concept is that management style contributes to improved financial reporting. Leadership style reflects a leader’s ability to plan and achieve specific goals and can be determined by the cohesiveness of the group or organization they lead. Leadership style refers to how leaders at the organizational or individual level influence and carry out their tasks. The research results indicate that management style influences financial reporting.